2016
DOI: 10.1038/srep21231
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of taurine biosynthesis in rainbow trout and Japanese flounder

Abstract: Animals have varied taurine biosynthesis capability, which was determined by activities of key enzymes including cysteine dioxygenase (CDO) and cysteine sulfinate decarboxylase (CSD). However, whether CDO and CSD are differentially regulated across species remains unexplored. In the present study, we examined the regulations of CDO and CSD in rainbow trout and Japanese flounder, the two fish species with high and low taurine biosynthesis ability respectively. Our results showed that the expression of CDO was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 55 publications
(96 reference statements)
1
34
0
Order By: Relevance
“…Hence, pathway 2 is also incapable of synthesizing taurine from its precursors in sufficient amounts. Supplementation of taurine precursors, such as methionine or cysteine, has been successful in stimulating the biosynthetic pathways in some (Yokoyama and Nakazoe ; Wang et al , ) but not all (Park et al ; Matsunari et al ) species. Moreover, in the former group, the improvement in growth performance is always limited and lower than that obtained through taurine supplementation (Jirsa et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, pathway 2 is also incapable of synthesizing taurine from its precursors in sufficient amounts. Supplementation of taurine precursors, such as methionine or cysteine, has been successful in stimulating the biosynthetic pathways in some (Yokoyama and Nakazoe ; Wang et al , ) but not all (Park et al ; Matsunari et al ) species. Moreover, in the former group, the improvement in growth performance is always limited and lower than that obtained through taurine supplementation (Jirsa et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The full mRNA sequence for Cdo was obtained with an ORF coding for a protein of 202 aa, whereas a partial ORF sequence of 166 aa was acquired for Ado. Alignment of aa from both genes revealed cupin motifs 1 and 2 separated by an intermotif region, which are common characteristics for cupin proteins (Dunwell et al, 2001;Wang et al, 2016). The partial ORF sequence coding for 176 aa found for csad contained the important pyridoxal-dependent decarboxylase conserved domain, an enzyme group which is also present in csad of Pagrus major, Seriola quinqueradiata, Oreochromis niloticus, and Oryzias latipes (Haga et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Aside from tauT, other genes in teleosts have been speculated to take part in taurine homeostasis, participating in the biosynthesis of this amino acid. In this respect, the regulation of taurine biosynthesis is complicated, as it is not only regulated by the product taurine but also the levels of substrate sulfur amino acids, with differential regulation of csad and cdo (Wang et al, 2016). It would be expected that both enzymes would be up-regulated when taurine levels were low/deficient, but this was not the case as peak mRNA copy numbers were observed in larvae fed tau1 with 3.7 mg taurine per g rotifers.…”
Section: Discussionmentioning
confidence: 99%
“…Functions of these genes included energy metabolism and nutrient absorption (e.g., vitamins, TCA cycle intermediates, taurine, and 3-hydroxybutyric acid), gut development (e.g., taurine, citrulline, and polyamines), and regulation of growth and development (e.g., citrulline, hydroxyproline, taurine). A better understanding for functions of genes involved in fish growth is needed because some metabolism pathways are found to be limited or even completely absent in fish due to the lack of host enzymes (for example, limited de novo synthesis of arginine in fish (Li et al, 2009 ), lack of nucleotides de novo synthesis in intestinal cells (Quan, 1992 ), and weak capacity of taurine biosynthesis in olive flounder (Wang et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, several studies have demonstrated the essentiality (i.e., improved growth and survival) of dietary taurine for many commercially relevant species, especially marine teleosts including olive flounder (Park et al, 2002 ; Kim et al, 2003 , 2008 ; Salze and Davis, 2015 ). Previous studies (Park et al, 2002 ; Wang et al, 2016 ) have demonstrated that olive flounder has a very weak taurine biosynthetic capability due to a mutation in enzyme cysteic acid decarboxylase (CAD). In the present study, KEGG analysis of L. lactis genome showed that it possessed genes encoding enzymes that might be involved in the biosynthesis of cysteic acid (Table 2) via serine/sulfate pathway (Machlin et al, 1955 ; Tevatia et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%